Two-photon excitation and luminescence of a CaWO4 scintillator - Mikhailik, V; Bailiff, I; Kraus, H; Rodnyi, P; Ninkovic, J (2004)
Luminescence of a CaWO4 scintillator was studied in the temperature range 77-500 K using intense laser excitation in the 450-600 nm spectral region. Characteristics of the observed blue emission are similar to those of the intrinsic luminescence of calcium tungstate. The emission is concluded to be caused by cascade excitation of CaWO4 that results in a two-photon excited (TPE) luminescence. The features of TPE luminescence of CaWO4 are analysed in comparison to those obtained with UV and X-ray excitation. (C) 2004 Elsevier Ltd. All rights reserved.